Humans, Dolphins, and Porpoises: Investigations at the Par-Tee Site, Seaside, Oregon, AD 100–800 - Hope Loiselle (Ethnobiology Letters, 2020)
Small cetaceans are understudied compared to whales and pinnipeds even though they represent a high-ranking prey choice when available in the environment. Building upon previous faunal analyses at the Par-Tee site, Seaside, Oregon that investigated whaling, this analysis of dolphin and porpoise remains suggests that people were hunting small cetaceans between AD 100–800 on the Oregon coast, especially harbor porpoise, which was found significantly more than any other cetacean species at the site. The quantity of small cetacean bone is unlikely to be the result of only acquiring stranded individuals. While there is no direct evidence of hunting, ethnographic literature and archaeologically recovered hunting technologies like harpoons provide insight into the means by which these species may have been hunted.